India's economy and growth : essays in honour of V.K.R.V. Rao - Nayak, Pulin; Goldar, Bishwanath; Agrawal, Pradeep; Rao, V. K. R. V. (Vijendra Kasturi Ranga Varadaraja), 1908-1991 (SAGE, 2010)
This is a collection of essays by 16 renowned Indian economists on contemporary issues linked to India's economic development. Among the topics covered in the essays are: structural breaks in the India growth process; relevance of the Solow growth model for a developing economy; sources of the growth acceleration in India from the 1980s and the contribution of sectoral changes to overall economic growth; constraints to achieving 4 per cent annual growth rate in agriculture; measurement of unorganized sector output, and savings and capital formation; ensuring environmental sustainability of the.